Bearing capacity of sandy soil treated by Kenaf fibre geotextile - Rashid, A.S.A. (Springer Verlag, 2017)
Bio-based materials are widely used recently in order to introduce a more sustainable construction material. Kenaf is a type of bio-based material that can be easily obtained in a tropical country, which could be a potential material to be utilised as a geotextile material because it has good tensile strength. The geotextile could be used to improve the bearing capacity of a loose soil. This paper presents a series of small-scale physical modelling tests to investigate the bearing capacity performance of Kenaf fibre geotextile laid on and inside the sand layer. A rigid footing was used to replicate a strip footing during the loading test, and sand was prepared based on 50 of relative density in a rigid testing chamber for ground model preparation. In order to treat the soil, Kenaf fibre geotextile was laid at four difference locations which are on the soil surface and underneath the ground model surface at 50, 75 and 100 mm deep. It was found that the usage of the Kenaf fibre geotextile has improved the bearing capacity of the sandy soil up to 414.9 as compared to untreated soil. It was also found that the depth of the Kenaf fibre geotextile treated into the soil also affects the soil performance. © 2017, Springer-Verlag GmbH Germany.